The Effect of Promotional Strategies, Pricing Strategies, and Perceived Product Quality on Consumer Purchase Intention of Glad2Glow Products via TikTok Shop as a Digital Marketing Platform - Putri Leoni; Septia Angraini Barus; Trendy Gabriel Sihombing; Ricky Rafii Ritonga; Zenni Riana (SEAN Institute, 2026)
This study aims to analyze the influence of promotional techniques, price considerations, and perceived product quality on consumer purchase intentions for Glad2Glow products through TikTok Shop. The study population consisted of individuals who had seen Glad2Glow product advertisements through TikTok Shop. Sampling was conducted purposively, involving 120 respondents. Data were collected using a survey and analyzed using multiple linear regression using SPSS software. The results showed that promotional techniques, pricing, and perceived product quality significantly influenced consumer purchase intentions. These findings indicate that purchase intentions can be enhanced through more effective digital marketing strategies, competitive pricing, and improved perceptions of product quality. These research findings offer important implications for marketing managers. First, companies need to focus on implementing attractive and relevant promotional techniques through digital platforms like TikTok Shop to attract consumers' attention. Second, competitive pricing that aligns with consumers' perceived value can increase product appeal and increase purchase intentions. Finally, companies should improve consumer perceived product quality, as perceived quality can strengthen loyalty and increase repeat purchases. Managers can leverage consumer data to optimize more personalized and effective marketing strategies on digital platforms.